Ophthalmic sustained-release adhesive gel containing copolymer and oleate and preparation process of ophthalmic sustained-release adhesive gel
The ophthalmic sustained-release adhesive gel, constructed through specific components and processes, solves the problem of unstable drug delivery networks in existing technologies, achieving stable drug release and long-term stability of the formulation, thus meeting the treatment needs of chronic eye diseases such as glaucoma.
Patent Information
- Application Number
- CN202512014809.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-01-30
AI Technical Summary
Existing ophthalmic sustained-release gel formulations have insufficient drug delivery network stability, resulting in unstable drug release. This makes it difficult to balance mechanical properties and long-term stability, and they fail to effectively meet the drug release requirements of chronic eye diseases such as glaucoma.
A drug-carrying network was constructed by synergistically using polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, oleate compounds, and structured phospholipids. Sodium hyaluronate and chitosan hydrochloride graft copolymer were combined as mucosal adhesion and penetration enhancers. An ophthalmic sustained-release adhesive gel was prepared through a specific process to ensure the synergistic effect of each component and form a stable drug-carrying system.
This approach achieves sustained and stable drug release, enhances the bioadhesion between the formulation and the ocular mucosa, prolongs the retention time and promotes drug penetration, ensures the mechanical properties and long-term stability of the formulation, and improves the consistency of therapeutic effects and medication safety.
Smart Images

Figure CN121421954A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of pharmaceutical formulation technology, and more specifically, to an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters and its preparation process. Background Technology
[0002] Ophthalmic sustained-release gel formulations are an important dosage form for treating chronic eye diseases such as glaucoma and dry eye. Their core purpose is to establish a sustained-release drug delivery system in the eye, prolonging drug retention time, maintaining effective blood drug concentrations, reducing dosing frequency, minimizing systemic side effects, and improving patient adherence. The key technology for these formulations lies in constructing a stable drug delivery network. This requires achieving sustained and stable drug release while ensuring the formulation itself possesses suitable mechanical properties to adapt to the ocular physiological environment, maintaining stability during long-term storage and use, and ensuring sustained and reliable therapeutic efficacy.
[0003] Most existing ophthalmic sustained-release gel formulations use a single polymer or a simple binary composite carrier to construct the drug delivery system. Due to the lack of precise synergistic effects between the components, it is difficult to form a dense and stable drug delivery network. This results in the formulations generally having problems such as large fluctuations in drug release rate and insufficient sustained-release period. Moreover, they often cannot balance drug release performance with the mechanical properties and long-term stability of the formulation. Some formulations have loose carrier structures that are easily degraded, leading to drug leakage and decreased mechanical strength after long-term storage, which affects the consistency of therapeutic effect and medication safety.
[0004] Even with attempts at optimization using relevant technologies, such as the patent document CN113559056A which discloses a thermosensitive in-situ gel formulation for ophthalmic use containing remdesivir, employing a polyethylene glycol-polypropylene glycol (PEG-PPG) block copolymer as the thermosensitive matrix and solving the problems of poor water solubility and short ocular retention time of lipid-soluble drugs by mixing micelles and gel, this technology still has significant limitations: it relies solely on a single thermosensitive block copolymer to construct the system, failing to form a stable drug-carrying network with multi-component synergy, making it difficult to balance sustained and stable drug release with long-term formulation stability; furthermore, its formulation and process are mainly optimized for antiviral drugs, without designing targeted mucosal adhesion and permeation-enhancing composite components, resulting in insufficient compatibility with prostaglandin drugs commonly used in chronic eye diseases such as glaucoma, and it does not prioritize the compatibility of formulation mechanical properties with the ocular physiological environment, thus failing to meet the high requirements for comprehensive formulation performance in the treatment of chronic eye diseases. Summary of the Invention
[0005] To address the problem that the drug-loaded network stability of existing ophthalmic sustained-release gel formulations is insufficient, leading to unstable drug release and difficulty in balancing mechanical properties and long-term stability, this application provides an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters, and a preparation process thereof.
[0006] In a first aspect, this application provides an ophthalmic sustained-release adhesive gel containing a copolymer and an oleate ester, employing the following technical solution: An ophthalmic sustained-release adhesive gel containing copolymers and oleate esters is made from the following components in parts by weight: 32-40 parts block copolymer, 3.0-5.0 parts oleate ester compound, 0.1-0.2 parts active pharmaceutical ingredient, 1.6-2.0 parts structured phospholipid, 1.2-1.6 parts mucosal adhesion and penetration enhancer, 0.6-1.0 parts antioxidant stabilizer, 4.0-6.0 parts osmotic pressure regulator, 1.3-1.5 parts pH adjuster, 0.02-0.06 parts preservative, and 600-660 parts water for injection.
[0007] By adopting the above technical solution, a sustained-release basic framework is constructed through block copolymers. Oleic acid ester compounds and structured phospholipids synergistically optimize the compatibility and dispersion stability of the drug delivery system, providing targeted therapeutic effects for the active drug. Mucosal adhesion and penetration enhancers strengthen the binding ability of the formulation to the ocular mucosa and assist drug penetration. Antioxidant stabilizers inhibit drug oxidation and formulation degradation. Osmotic pressure regulators adjust the osmotic pressure of the formulation to adapt to the physiological environment of the eye. pH regulators maintain the acid-base range of the formulation suitable for the eye. Preservatives inhibit microbial growth to ensure safe use. Water for injection serves as the dispersion and dissolution medium for each component. The components work synergistically in a specific ratio to form a complete ophthalmic sustained-release gel system, thereby achieving the effect of stable coexistence of each functional component, adapting to the physiological needs of the eye, and providing a material basis for the subsequent realization of core performances such as sustained release and enhanced penetration.
[0008] Preferably, it is made from the following components in parts by weight: 36 parts block copolymer, 4.0 parts oleate compound, 0.15 parts active pharmaceutical ingredient, 1.8 parts structured phospholipid, 1.4 parts mucosal adhesion and penetration enhancer, 0.8 parts antioxidant stabilizer, 5.0 parts osmotic pressure regulator, 1.4 parts pH regulator, 0.04 parts preservative, and 375 parts water for injection.
[0009] Preferably, the block copolymer is a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the mass ratio of polycaprolactone segments to polyethylene glycol segments is 1.8:1 to 2.5:1, and the number average molecular weight of the polyethylene glycol segments is 1500-2500; the oleate compound is p-hydroxyphenylethanol oleate; and the structured phospholipid is distearylphosphatidylethanolamine-polyethylene glycol 2000.
[0010] By employing the above technical solutions, a well-structured gel framework is constructed by selecting a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer and limiting the specific mass ratio of polycaprolactone to polyethylene glycol segments and the number-average molecular weight range of polyethylene glycol segments. This is achieved by utilizing the appropriate ratio of hydrophobic polycaprolactone segments to hydrophilic polyethylene glycol segments, while simultaneously adjusting the affinity / reactivity of the framework using polyethylene glycol segments of specific molecular weights. Furthermore, by selecting p-hydroxyphenylethanol oleate as an oleate compound, the phenylethanol groups in its molecular structure enhance the interaction with other components. Finally, by selecting distearylphosphatidylethanolamine-polyethylene glycol 2000 as a structured phospholipid, the steric hindrance effect of its PEG-modified groups is utilized. These three components synergistically optimize component compatibility and promote stable dispersion formation, thereby achieving the effect of constructing a uniform and stable drug-loaded matrix for formulations and precisely regulating gel performance.
[0011] Preferably, the active pharmaceutical ingredient is at least one of latanoprost, tafluprost, or bemexprost; and the antioxidant stabilizer is at least one of DL-α-tocopherol polyethylene glycol succinate or sodium bisulfite.
[0012] By adopting the above technical solutions, and selecting latanoprost, tafluprost, or bimeprost as active drugs, their specific pharmacological activities are used to target ocular targets. By selecting DL-α-tocopherol polyethylene glycol succinate or sodium bisulfite as antioxidant stabilizers, their antioxidant activities are used to inhibit drug oxidation and degradation of formulation components. Through synergistic adaptation to the sustained-release system of the formulation, the effects of ensuring drug therapeutic targeting, enhancing the formulation's mucosal retention and permeation effects, and maintaining the stability of the formulation during storage and use are achieved.
[0013] Preferably, the mucosal adhesion and penetration enhancer is a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds, with a number-average molecular weight of 8,000-20,000, and the mass ratio of sodium hyaluronate to chitosan hydrochloride is 1:0.5 to 1:2; the osmotic pressure regulator is at least one of sodium chloride and mannitol; the pH regulator is at least one of disodium hydrogen phosphate-sodium dihydrogen phosphate buffer pair and triethanolamine, used to adjust and maintain the pH of the formulation at 6.8-7.2; and the preservative is at least one of benzalkonium chloride, potassium sorbate, or phenoxyethanol.
[0014] By employing the above technical solutions, a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds is selected as a mucosal adhesion and penetration enhancer, and its specific number-average molecular weight range is defined. The stabilizing effect of the amide bonds enhances the structural stability of the complex, ensuring a balance between adhesion performance and penetration efficiency within a specific molecular weight range. Sodium chloride or mannitol is selected as an osmotic pressure regulator, utilizing its osmotic pressure regulating properties to match the osmotic pressure of the formulation with the physiological environment of the eye. Disodium hydrogen phosphate-sodium dihydrogen phosphate buffer pair or triethanolamine is selected as a pH regulator, utilizing its buffering capacity to stabilize the pH of the formulation within the eye's tolerance range. Benzalkonium chloride, potassium sorbate, or phenoxyethanol is selected as a preservative, relying on its antibacterial activity to inhibit the growth of microorganisms in the formulation. Each component is specifically adapted to the physiological needs of the eye and the formulation system, thereby achieving the effects of reducing eye irritation, enhancing the biocompatibility of the formulation, and ensuring safety in use and storage stability.
[0015] Secondly, this application provides a preparation process for an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters, using the following technical solution: A process for preparing an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters includes the following steps: S1. Preparation of co-assembled dispersion: The oleate compound and the structured phospholipid were dissolved together in anhydrous ethanol. The solution was injected into preheated water for injection under nitrogen protection, and then subjected to high-pressure microfluidic homogenization to obtain the dispersion. S2. Chemical treatment of active drugs: The active drugs are dissolved in ethanol, and the solution is added dropwise to a portion of water for injection under ice bath and ultrasonic assistance. Then, high pressure homogenization is performed to obtain a drug suspension. S3. Swelling and formation of gel matrix: The block copolymer is dispersed in the remaining water for injection, allowed to swell at low temperature, and then stirred under heating conditions to form a uniform and transparent gel matrix solution. S4. Stepwise mixing: First, mix and stir the dispersion with the gel matrix solution, then slowly add the drug suspension dropwise to the mixture. After the addition is complete, cool and stir to homogenize. S5. Integration of functional excipients and ultrasonic treatment: The formulation amounts of the mucosal adhesion and penetration enhancer, antioxidant stabilizer, osmotic pressure regulator and preservative are added to the mixture in sequence. Each excipient is stirred separately until dissolved or dispersed after being added. Then the whole system is subjected to intermittent ultrasonic treatment in an ice water bath. S6. pH adjustment and programmed maturation: Add a pH adjuster to adjust the pH value of the system to the range suitable for eye use, then first allow it to mature at a low temperature, and then program the temperature to be increased to near body temperature for further maturation. S7. Terminal sterilization and dispensing: The matured gel is filtered through two stages of microporous membranes for sterilization, then filled and sealed with nitrogen in a sterile environment.
[0016] By employing the above technical solution, a stable dispersion is prepared by first dissolving oleate compounds and structured phospholipids in anhydrous ethanol, injecting them into preheated water for injection under nitrogen protection, and homogenizing them using high-pressure microfluidic jets. Then, the active drug is dissolved in ethanol, added dropwise with ice bath ultrasonic assistance, and homogenized under high pressure. Simultaneously, the block copolymer is swelled at low temperature and stirred at elevated temperature to form a homogeneous gel matrix. Subsequently, a step-by-step mixing mode is used to first fuse the dispersion and gel matrix, then the drug suspension is slowly added and homogenized while cooling. Functional excipients are added sequentially, dissolved separately by stirring, and then subjected to intermittent ultrasonic treatment in an ice-water bath. Finally, after pH adjustment, the structure is optimized through a programmed maturation process combining low-temperature static incubation and programmed temperature rise. The mixture is then filtered through two-stage microporous membranes for sterilization and sealed with nitrogen to complete the preparation. Each step specifically treats different components. By precisely controlling key stages such as dispersion, mixing, and maturation, component aggregation is avoided, uniform fusion of components is ensured, and the gel network structure is optimized, thereby achieving the effect of constructing a stable drug-loaded system and ensuring the homogeneity and performance stability of the formulation.
[0017] Preferably, in step S1, the temperature of the preheated water for injection is 50-60℃, and its amount accounts for 25-35% of the total weight of the water for injection; the pressure of the high-pressure microfluidic homogenization treatment is 80-120MPa, and the number of cycles is 3-4; the volume of anhydrous ethanol used is 4-6 times the total mass of the oleate compound and the structured phospholipid; in step S2, the volume of ethanol used to dissolve the active drug is 8-12 times the weight of the active drug; the portion of water for injection accounts for 10-15% of the total weight of the water for injection; the pressure of the high-pressure homogenization treatment is 60-100MPa, and the number of treatments is 2-4.
[0018] By adopting the above technical solution, in step S1, the temperature range of 50-60℃ for preheating the water for injection and the dosage ratio of 25-35% of the total weight of the water for injection are clearly defined, providing a suitable dispersion environment for the anhydrous ethanol solution of oleate compounds and structured phospholipids, ensuring that the oil phase components are uniformly spread in the aqueous phase; high-pressure micro-jet homogenization treatment with a pressure of 80-120MPa and 3-4 cycles is combined with anhydrous ethanol equivalent to 4-6 times the total mass of oleate compounds and structured phospholipids, breaking the component aggregation tendency through sufficient shear force and solvent compatibility; in step S2, ethanol with a volume of 8-12 times the weight of the active drug is used to ensure that the drug is fully dissolved, and a mild dispersion system is constructed with a portion of the water for injection accounting for 10-15% of the total weight of the water for injection, combined with high-pressure homogenization with a pressure of 60-100MPa and 2-4 cycles and ice bath ultrasonic assistance, to enhance the fineness effect of drug particles. The precise matching of these parameters plays a role in synergistically regulating the particle size of the dispersion and improving the uniformity of component dispersion, thereby providing a stable dispersion phase for the subsequent gel system and ensuring the uniformity of drug loading.
[0019] Preferably, in step S3, the low temperature is 4-8℃, and the swelling time is 3-5 hours; the heating condition is 35-40℃, and the stirring speed is 300-400 rpm; in step S4, the mixing temperature of the dispersion and the gel matrix solution is 35-40℃, and the stirring time is 1-2 hours; after the addition, the temperature is lowered to 20-25℃, the stirring rate is 500-600 rpm, and the homogenization time is 1-1.5 hours.
[0020] By employing the above technical solution, in step S3, a low-temperature environment of 4-8℃ and a swelling time of 3-5 hours are defined to allow the block copolymer to be fully dispersed and slowly swell to avoid aggregation. Then, a suitable heating condition of 35-40℃ combined with a stirring speed of 300-400 rpm promotes the orderly cross-linking of the swollen copolymer to form a uniform and transparent gel matrix. In step S4, mixing is carried out at 35-40℃, matching the gel matrix formation temperature, and maintained for 1-2 hours to ensure full integration of the dispersion and the gel matrix. After adding the drug suspension, the temperature is lowered to 20-25℃, and homogenization is performed at 500-600 rpm for 1-1.5 hours to reduce the impact of high temperature on the system stability and promote uniform drug dispersion. The synergistic setting of these parameters ensures a regular gel matrix structure and promotes the orderly compatibility of each component, thereby improving the uniformity of the gel system and ensuring uniform drug loading.
[0021] Preferably, in step S5, the speed of the individual stirring is 200-300 rpm and the time is 15-25 minutes; the power of the intermittent ultrasonic treatment is 150-250W and the frequency is 25-35kHz, using a mode of working for 2-3 seconds and intermittent for 3-4 seconds, with a total treatment time of 8-15 minutes.
[0022] By adopting the above technical solution, and setting a separate stirring speed of 200-300 rpm and a stirring time of 15-25 minutes in step S5, each functional excipient can be fully dissolved or uniformly dispersed after being added to the mixing system, avoiding local aggregation of excipients due to insufficient stirring intensity or time. Simultaneously, intermittent ultrasonic treatment at a power of 150-250W and a frequency of 25-35kHz, using a 2-3 second working and 3-4 second intermittent mode, and controlling the total treatment time to 8-15 minutes, both utilizes ultrasonic energy to refine the dispersion state of the system and avoids the impact of continuous ultrasonic heat generation on system stability through the intermittent mode. This precise combination of parameters ensures full compatibility between the functional excipients and the gel system, avoids local unevenness, and thus improves the overall dispersion uniformity of the formulation, laying the foundation for the efficient performance of each function.
[0023] Preferably, in step S6, the applicable pH range for the eye is 6.9-7.1; the low-temperature curing process is carried out at 4-6℃ for 8-12 hours; the programmed temperature rise rate is 0.2-0.5℃ / min, the near-body temperature is 25-30℃, and the curing time is 2-4 hours; in step S7, the two-stage microporous filter membrane is a 0.45μm and 0.22μm polyethersulfone filter membrane; the container is purged with nitrogen three times before filling, each purging lasting 10-15 seconds.
[0024] By adopting the above technical solution, and by limiting the applicable pH range for the eye to 6.9-7.1 in step S6, the pH of the formulation is precisely matched to the physiological tolerance range of the eye. The gel system is then allowed to mature at a low temperature of 4-6℃ for 8-12 hours, allowing the internal components to slowly adjust their arrangement. The temperature is then gradually increased to a near-body temperature of 25-30℃ at a slow rate of 0.2-0.5℃ / min, and maturation continues for 2-4 hours to avoid defects in the gel network caused by sudden temperature changes. In step S7, two-stage gradient filtration is performed using 0.45μm and 0.22μm polyethersulfone membranes. Simultaneously, the container is purged with nitrogen three times, each time for 10-15 seconds, before filling. These parameters and operational settings optimize the gel network structure, ensure the sterility of the formulation, and reduce the risk of oxidative degradation, thereby achieving the effect of making the formulation more suitable for the physiological environment of the eye, with a more stable structure, and safer use.
[0025] In summary, this application has the following beneficial effects: 1. This application uses polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, p-hydroxyphenylethanol oleate, and distearate phosphatidylethanolamine-polyethylene glycol 2000 to form a specific ternary composite carrier. In this system, the block copolymer provides a sustained-release skeleton, the phenylethanol structure of the oleate enhances the synergistic effect, and the structured phospholipid improves the stability of the system. The three work together to construct a dense and stable drug-carrying network, thus achieving the beneficial effects of sustained and stable drug release, while taking into account the mechanical properties and long-term stability of the formulation.
[0026] 2. In this application, a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds is preferably used as a mucosal adhesion and penetration enhancer. Because this chemical graft structure combines the lubricating and moisturizing properties of hyaluronic acid with the cationic mucosal adhesion properties of chitosan, a synergistic effect that is difficult to achieve with a single component is formed, which enhances the bioadhesion of the formulation to the ocular mucosa. Therefore, the beneficial effects of significantly prolonging the retention time of the formulation on the corneal surface and promoting drug penetration are obtained.
[0027] 3. The method of this application, through a process of first constructing a co-assembled dispersion and drug suspension and then performing a stepwise mixing process, and finally adopting a programmed ripening treatment, ensures that each functional component is integrated in an orderly manner, avoids phase separation and promotes the formation of a uniform and stable three-dimensional gel network. Therefore, it achieves the beneficial effects of uniform formulation structure, good reproducibility and high storage stability. Attached Figure Description
[0028] Figure 1 This is a process flow diagram of the preparation of an ophthalmic sustained-release adhesive gel containing copolymer and oleate ester provided in this application. Detailed Implementation
[0029] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.
[0030] Technical concept: In related technologies, ophthalmic sustained-release gel formulations suffer from unstable drug release and difficulty in balancing mechanical properties and long-term stability. The core reason is that existing formulations mostly use single polymers or simple binary composite carriers to construct the system, lacking precise compatibility and synergistic effects between components, resulting in a loose drug-loaded network structure and insufficient stability. Simultaneously, the compatibility between the drug and the carrier is poor, leading to aggregation during dispersion. The structural regularity during gel framework formation is difficult to control, thus affecting the controllability of drug release. Furthermore, component separation and performance degradation are prone to occur during long-term storage.
[0031] This technical solution addresses the aforementioned issues by constructing a specific ternary composite carrier system. It utilizes a synergistic effect of polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, p-hydroxyphenylethanol oleate, and distearate phosphatidylethanolamine-polyethylene glycol 2000 to form a dense and stable drug-carrying network through the structural characteristics of each component. Simultaneously, it optimizes the types and ratios of functional components such as mucosal adhesion and penetration enhancers, coupled with a customized preparation process. Through key steps including co-assembly dispersion preparation, stepwise mixing, intermittent ultrasonic treatment, and programmed maturation, combined with precise control of process parameters, it ensures uniform dispersion of components and the formation of a well-organized gel network. Ultimately, this achieves a synergistic improvement in drug release stability and formulation mechanical properties and long-term stability.
[0032] Preparation Example 1 The preparation method of the graft copolymer of sodium hyaluronate and chitosan hydrochloride is as follows: Dissolve 10g of sodium hyaluronate in 1000mL of deionized water and stir at 300rpm for 30 minutes at room temperature until completely dissolved, forming a homogeneous and transparent solution. Separately, dissolve 10g of chitosan hydrochloride in 1000mL of 5% dilute acetic acid solution and stir at 50℃ for 20 minutes until dissolved. Then adjust the pH of the system to 5.0 with 10% sodium hydroxide solution. Under stirring conditions of 25℃ and 300rpm, slowly add the chitosan hydrochloride solution dropwise to the sodium hyaluronate solution at a rate of 5mL / min. After the addition is complete, add 2.5g of 1-ethyl-3-dimethylaminopropylcarbodiimide hydrochloride and 1.5g of N-hydroxysuccinimide. Continue stirring and reacting for 18 hours in the dark. After the reaction is complete, transfer the reaction solution to a dialysis bag with a molecular weight cutoff of 3500Da and dialyze with deionized water for 3 days, changing the dialysate 3 times daily to remove unreacted raw materials and small molecule byproducts. Finally, the dialysate was placed in a freeze dryer and dried at -50°C and a vacuum of less than 10 Pa for 24 hours to obtain a white, spongy graft copolymer solid of sodium hyaluronate and chitosan hydrochloride linked by amide bonds.
[0033] Preparation Example 2 The preparation method of p-hydroxyphenylethanol oleic acid is as follows: In a 250 mL three-necked flask equipped with a water separator, condenser, and thermometer, 28.2 g of oleic acid, 16.6 g of p-hydroxyphenylethanol, 0.5 g of p-toluenesulfonic acid, and 150 mL of toluene were added, with toluene acting as a dehydrating agent. Nitrogen gas was purged into the flask three times to purge the air. The reaction mixture was then heated to 115 °C and refluxed, with continuous stirring for 7 hours. During this time, approximately 1.8 mL of water was separated using the water separator. After the reaction was complete, the system was cooled to room temperature and washed twice with 100 mL of saturated sodium bicarbonate solution and then with 100 mL of deionized water until the pH of the aqueous phase reached 7.0. The organic layer was dried for 2 hours with 5 g of anhydrous sodium sulfate, and the desiccant was removed by filtration. The filtrate was then distilled under reduced pressure at 80 °C and a vacuum of 50 Pa to remove toluene, yielding a pale yellow, oily crude product. The crude product was purified by silica gel column chromatography with a diameter of 5 cm and a height of 30 cm. The eluent was a mixture of petroleum ether and ethyl acetate in a volume ratio of 5:1. The eluent corresponding to the target component was collected and concentrated again under reduced pressure to remove the solvent, yielding pure, colorless, transparent, oily p-hydroxyphenylethanol oleic acid.
[0034] Preparation Example 3 Preparation of polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer 10 g of polyethylene glycol with a number average molecular weight of 2000 was added to a 500 mL three-necked flask and dehydrated under reduced pressure at 120 °C and 50 Pa for 2 hours to remove moisture from the raw material. After cooling to 80 °C, 21.5 g of ε-caprolactone purified by reduced pressure distillation was added, wherein the mass ratio of polycaprolactone segments to polyethylene glycol segments was 2.15:1. Then, 0.05 g of stannous octoate was added as a catalyst, and the mixture was stirred until homogeneous.
[0035] The air in the flask was purged with nitrogen three times to maintain a nitrogen atmosphere. The reaction system was heated to 130°C and polymerized by stirring at 200 rpm for 12 hours. After the polymerization reaction was completed, the system was cooled to 60°C, and 200 mL of anhydrous diethyl ether was added and stirred to dissolve the product. The mixture was then allowed to cool to room temperature, resulting in the precipitation of a white solid. The solid product was collected by filtration and washed three times with 50 mL of anhydrous diethyl ether each time to remove unreacted ε-caprolactone monomer and catalyst residue.
[0036] The washed solid was placed in a vacuum drying oven and dried at 60°C and 50 Pa for 8 hours to obtain a white flocculent polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer. Gel permeation chromatography determined that the copolymer had a number-average molecular weight of 8300 and a polycaprolactone to polyethylene glycol mass ratio of 2.15:1.
[0037] The following are the main raw materials and reagents used in the preparation examples, embodiments, and comparative examples, and their sources and specifications are as follows; unless otherwise specified, all reagents are commercially available analytical grade or higher products: 1. Distearylphosphatidylethanolamine-polyethylene glycol 2000 was purchased from Hubei Weishi Chemical Reagent Co., Ltd., product number: HBWS-66; 2. Sodium hyaluronate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S12034; 3. Chitosan hydrochloride was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S28548; 4. DL-α-tocopherol polyethylene glycol succinate was purchased from Shanghai Mairui Biochemical Technology Co., Ltd., item number: M65399; 5. Mannitol was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S11072; 6. Triethanolamine was purchased from Jinan Jinhao Chemical Co., Ltd., CAS: 102-71-6; 7. Benzalkonium chloride was purchased from Xi'an Xinfengda Pharmaceutical Excipients Co., Ltd., CAS: 139-07-1; 8. Potassium sorbate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S11114; 9. Phenoxyethanol was purchased from Nanjing Chemical Reagent Co., Ltd., CAS: 122-99-6.
[0038] Example 1 This application provides an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters, which is made of the following components in parts by weight: 36 parts of block copolymer, 4.0 parts of oleate ester compound, 0.15 parts of active pharmaceutical ingredient, 1.8 parts of structured phospholipid, 1.4 parts of mucosal adhesion and penetration enhancer, 0.8 parts of antioxidant stabilizer, 5.0 parts of osmotic pressure regulator, 1.4 parts of pH regulator, 0.04 parts of preservative, and 375 parts of water for injection.
[0039] The block copolymer is a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the mass ratio of polycaprolactone segments to polyethylene glycol segments is 2.15:1, and the number average molecular weight of polyethylene glycol segments is 2000. Among them, the oleate compound is p-hydroxyphenylethanol oleate; Among them, the structured phospholipid is distearylphosphatidylethanolamine-polyethylene glycol 2000; Among them, the mucosal adhesion and penetration enhancer is a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds, with a number average molecular weight of 8,000-20,000 and a mass ratio of sodium hyaluronate to chitosan hydrochloride of 1:1. The active drug is latanoprost. The antioxidant stabilizer is DL-α-tocopherol polyethylene glycol succinate. The osmotic pressure regulator is sodium chloride; The pH adjuster is a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer pair. The preservative is benzalkonium chloride.
[0040] The preparation process of the above-mentioned ophthalmic sustained-release adhesive gel containing copolymer and oleate includes the following steps: S1. Preparation of co-assembled dispersion: The oleate compound and the structured phospholipid were dissolved together in anhydrous ethanol. The solution was injected into preheated water for injection under nitrogen protection, and then subjected to high-pressure microfluidic homogenization to obtain the dispersion. The temperature of the preheated water for injection is 55°C, and its usage accounts for 30% of the total weight of the water for injection; the pressure of the high-pressure microfluidic homogenization treatment is 100 MPa, and the number of cycles is 4; the volume of the anhydrous ethanol used is 5 times the total mass of the oleate compound and the structured phospholipid.
[0041] S2. Chemical treatment of active drugs: The active drugs are dissolved in ethanol, and the solution is added dropwise to a portion of water for injection under ice bath and ultrasonic assistance. Then, high pressure homogenization is performed to obtain a drug suspension. The volume of ethanol used to dissolve the active drug is 10 times the weight of the active drug; the portion of water for injection accounts for 12.5% of the total weight of water for injection; the pressure of the high-pressure homogenization treatment is 80 MPa, and the treatment is performed 3 times.
[0042] S3. Swelling and formation of gel matrix: The block copolymer is dispersed in the remaining water for injection, allowed to swell at low temperature, and then stirred under heating conditions to form a uniform and transparent gel matrix solution. The low temperature was 6℃, and the swelling time was 4 hours; the heating conditions were 37℃ and the stirring speed was 350 rpm.
[0043] S4. Stepwise mixing: First, mix and stir the dispersion with the gel matrix solution, then slowly add the drug suspension dropwise to the mixture. After the addition is complete, cool and stir to homogenize. The mixing temperature of the dispersion and the gel matrix solution was 37℃, and the stirring time was 1.5 hours. After the addition, the temperature was lowered to 22℃, the stirring rate was 550 rpm, and the homogenization time was 1.25 hours.
[0044] S5. Integration of functional excipients and ultrasonic treatment: The formulation amounts of the mucosal adhesion and penetration enhancer, antioxidant stabilizer, osmotic pressure regulator and preservative are added to the mixture in sequence. Each excipient is stirred separately until dissolved or dispersed after being added. Then the whole system is subjected to intermittent ultrasonic treatment in an ice water bath. The stirring speed was 250 rpm and the time was 20 minutes; the intermittent ultrasonic treatment had a power of 200W and a frequency of 30kHz, using a mode of working for 2.5 seconds and intermittent for 3.5 seconds, with a total treatment time of 12 minutes.
[0045] S6. pH adjustment and programmed maturation: Add a pH adjuster to adjust the pH value of the system to the range suitable for eye use, then first allow it to mature at a low temperature, and then program the temperature to be increased to near body temperature for further maturation. The applicable pH range for eye use is 7.0; the low-temperature static curing process involves standing at 5°C for 10 hours; the programmed temperature rise rate is 0.35°C / min, the near-body temperature is 27°C, and the continued curing time is 3 hours.
[0046] S7. Terminal sterilization and dispensing: The matured gel is filtered through two stages of microporous membranes for sterilization, then filled and sealed with nitrogen in a sterile environment.
[0047] The two-stage microporous filter membranes are polyethersulfone filter membranes with diameters of 0.45 μm and 0.22 μm; the container is purged with nitrogen three times before filling, with each purging lasting 12 seconds.
[0048] Example 2 This application provides an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters, which is made of the following components in parts by weight: 32 parts of block copolymer, 3.0 parts of oleate ester compound, 0.1 parts of active drug, 1.6 parts of structured phospholipid, 1.2 parts of mucosal adhesion and penetration enhancer, 0.6 parts of antioxidant stabilizer, 4.0 parts of osmotic pressure regulator, 1.3 parts of pH regulator, 0.02 parts of preservative, and 350 parts of water for injection.
[0049] The block copolymer is a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the mass ratio of polycaprolactone segments to polyethylene glycol segments is 1.8:1, and the number average molecular weight of polyethylene glycol segments is 1500. Among them, the oleate compound is p-hydroxyphenylethanol oleate; Among them, the structured phospholipid is distearylphosphatidylethanolamine-polyethylene glycol 2000; Among them, the mucosal adhesion and penetration enhancer is a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds, with a number average molecular weight of 8,000-20,000, and a mass ratio of sodium hyaluronate to chitosan hydrochloride of 1:0.5. The active drug is tafluprost; The antioxidant stabilizer is sodium bisulfite. The osmotic pressure regulator is mannitol. The pH adjuster is triethanolamine. The preservative is potassium sorbate.
[0050] The preparation process of the above-mentioned ophthalmic sustained-release adhesive gel containing copolymer and oleate includes the following steps: S1. Preparation of co-assembled dispersion: The oleate compound and the structured phospholipid were dissolved together in anhydrous ethanol. The solution was injected into preheated water for injection under nitrogen protection, and then subjected to high-pressure microfluidic homogenization to obtain the dispersion. The temperature of the preheated water for injection is 50°C, and its usage accounts for 25% of the total weight of the water for injection; the pressure of the high-pressure microfluidic homogenization treatment is 80 MPa, and the number of cycles is 3; the volume of the anhydrous ethanol used is 4 times the total mass of the oleate compound and the structured phospholipid.
[0051] S2. Chemical treatment of active drugs: The active drugs are dissolved in ethanol, and the solution is added dropwise to a portion of water for injection under ice bath and ultrasonic assistance. Then, high pressure homogenization is performed to obtain a drug suspension. The volume of ethanol used to dissolve the active drug is 8 times the weight of the active drug; the portion of water for injection accounts for 10% of the total weight of water for injection; the pressure of the high-pressure homogenization treatment is 60 MPa, and the treatment is performed twice.
[0052] S3. Swelling and formation of gel matrix: The block copolymer is dispersed in the remaining water for injection, allowed to swell at low temperature, and then stirred under heating conditions to form a uniform and transparent gel matrix solution. The low temperature was 4℃, and the swelling time was 3 hours; the heating condition was 35℃, and the stirring speed was 300 rpm.
[0053] S4. Stepwise mixing: First, mix and stir the dispersion with the gel matrix solution, then slowly add the drug suspension dropwise to the mixture. After the addition is complete, cool and stir to homogenize. The mixing temperature of the dispersion and the gel matrix solution was 35℃, and the stirring time was 1 hour. After the addition, the temperature was lowered to 20℃, the stirring rate was 500 rpm, and the homogenization time was 1 hour.
[0054] S5. Integration of functional excipients and ultrasonic treatment: The formulation amounts of the mucosal adhesion and penetration enhancer, antioxidant stabilizer, osmotic pressure regulator and preservative are added to the mixture in sequence. Each excipient is stirred separately until dissolved or dispersed after being added. Then the whole system is subjected to intermittent ultrasonic treatment in an ice water bath. The stirring speed was 200 rpm and the time was 15 minutes; the intermittent ultrasonic treatment had a power of 150W and a frequency of 25kHz, using a mode of working for 2 seconds and intermittently for 3 seconds, with a total treatment time of 8 minutes.
[0055] S6. pH adjustment and programmed maturation: Add a pH adjuster to adjust the pH value of the system to the range suitable for eye use, then first allow it to mature at a low temperature, and then program the temperature to be increased to near body temperature for further maturation. The applicable pH range for eye use is 6.9; the low-temperature static curing process involves standing at 4°C for 8 hours; the programmed temperature rise rate is 0.2°C / min, the near-body temperature is 25°C, and the continued curing time is 2 hours.
[0056] S7. Terminal sterilization and dispensing: The matured gel is filtered through two stages of microporous membranes for sterilization, then filled and sealed with nitrogen in a sterile environment.
[0057] The two-stage microporous filter membranes are polyethersulfone filter membranes with diameters of 0.45 μm and 0.22 μm; the container is purged with nitrogen three times before filling, with each purging lasting 10 seconds.
[0058] Example 3 This application provides an ophthalmic sustained-release adhesive gel containing copolymers and oleate esters, which is made of the following components in parts by weight: 40 parts of block copolymer, 5.0 parts of oleate ester compound, 0.2 parts of active drug, 2.0 parts of structured phospholipid, 1.6 parts of mucosal adhesion and penetration enhancer, 1.0 part of antioxidant stabilizer, 6.0 parts of osmotic pressure regulator, 1.5 parts of pH regulator, 0.06 parts of preservative, and 400 parts of water for injection.
[0059] The block copolymer is a polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the mass ratio of polycaprolactone segments to polyethylene glycol segments is 2.5:1, and the number average molecular weight of polyethylene glycol segments is 2500. Among them, the oleate compound is p-hydroxyphenylethanol oleate; Among them, the structured phospholipid is distearylphosphatidylethanolamine-polyethylene glycol 2000; Among them, the mucosal adhesion and penetration enhancer is a graft copolymer of sodium hyaluronate and chitosan hydrochloride linked by amide bonds, with a number average molecular weight of 8,000-20,000 and a mass ratio of sodium hyaluronate to chitosan hydrochloride of 1:2. The active drug is bermuda prostol; The antioxidant stabilizer is DL-α-tocopherol polyethylene glycol succinate. The osmotic pressure regulator is sodium chloride; The pH adjuster is a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer pair. The preservative is phenoxyethanol.
[0060] The preparation process of the above-mentioned ophthalmic sustained-release adhesive gel containing copolymer and oleate includes the following steps: S1. Preparation of co-assembled dispersion: The oleate compound and the structured phospholipid were dissolved together in anhydrous ethanol. The solution was injected into preheated water for injection under nitrogen protection, and then subjected to high-pressure microfluidic homogenization to obtain the dispersion. The temperature of the preheated water for injection is 60°C, and its usage accounts for 35% of the total weight of the water for injection; the pressure of the high-pressure microfluidic homogenization treatment is 120 MPa, and the number of cycles is 4; the volume of the anhydrous ethanol used is 6 times the total mass of the oleate compound and the structured phospholipid.
[0061] S2. Chemical treatment of active drugs: The active drugs are dissolved in ethanol, and the solution is added dropwise to a portion of water for injection under ice bath and ultrasonic assistance. Then, high pressure homogenization is performed to obtain a drug suspension. The volume of ethanol used to dissolve the active drug is 12 times the weight of the active drug; the portion of water for injection accounts for 15% of the total weight of water for injection; the pressure of the high-pressure homogenization treatment is 100 MPa, and the treatment is performed 4 times.
[0062] S3. Swelling and formation of gel matrix: The block copolymer is dispersed in the remaining water for injection, allowed to swell at low temperature, and then stirred under heating conditions to form a uniform and transparent gel matrix solution. The low temperature was 8℃, and the swelling time was 5 hours; the heating condition was 40℃, and the stirring speed was 400 rpm.
[0063] S4. Stepwise mixing: First, mix and stir the dispersion with the gel matrix solution, then slowly add the drug suspension dropwise to the mixture. After the addition is complete, cool and stir to homogenize. The mixing temperature of the dispersion and the gel matrix solution was 40℃, and the stirring time was 2 hours. After the addition, the temperature was lowered to 25℃, the stirring rate was 600 rpm, and the homogenization time was 1.5 hours.
[0064] S5. Integration of functional excipients and ultrasonic treatment: The formulation amounts of the mucosal adhesion and penetration enhancer, antioxidant stabilizer, osmotic pressure regulator and preservative are added to the mixture in sequence. Each excipient is stirred separately until dissolved or dispersed after being added. Then the whole system is subjected to intermittent ultrasonic treatment in an ice water bath. The stirring speed was 300 rpm and the time was 25 minutes; the intermittent ultrasonic treatment had a power of 250W and a frequency of 35kHz, using a 3-second working and 4-second intermittent mode, with a total treatment time of 15 minutes.
[0065] S6. pH adjustment and programmed maturation: Add a pH adjuster to adjust the pH value of the system to the range suitable for eye use, then first allow it to mature at a low temperature, and then program the temperature to be increased to near body temperature for further maturation. The applicable pH range for eye use is 7.1; the low-temperature static curing process involves standing at 6°C for 12 hours; the programmed temperature rise rate is 0.5°C / min, the near-body temperature is 30°C, and the curing time is 4 hours.
[0066] S7. Terminal sterilization and dispensing: The matured gel is filtered through two stages of microporous membranes for sterilization, then filled and sealed with nitrogen in a sterile environment.
[0067] The two-stage microporous filter membranes are polyethersulfone filter membranes with diameters of 0.45 μm and 0.22 μm; the container is purged with nitrogen three times before filling, with each purging lasting 15 seconds.
[0068] Comparative Example 1 The only difference between this comparative example and Example 1 is that no oleate compound is added, that is, the formulation does not contain this component. The types, amounts and preparation processes of the other components are exactly the same as those in Example 1.
[0069] Comparative Example 2 The only difference between this comparative example and Example 1 is that the oleate compound p-hydroxyphenylethanol oleate is replaced with an equimolar amount of ethyl oleate. The other components, amounts, and preparation processes are exactly the same as in Example 1.
[0070] Comparative Example 3 The only difference between this comparative example and Example 1 is that structured phospholipids are not added, meaning that the formulation does not contain this component. The types, amounts, and preparation processes of the other components are exactly the same as in Example 1.
[0071] Comparative Example 4 The only difference between this comparative example and Example 1 is that the structured phospholipid distearate phosphatidylethanolamine-polyethylene glycol 2000 is replaced with an equal mass of ordinary soybean lecithin. The other components, dosages, and preparation processes are exactly the same as in Example 1.
[0072] Comparative Example 5 The only difference between this comparative example and Example 1 is that the block copolymer polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer is replaced with an equal mass of poloxamer 407, which has similar temperature-sensitive properties. The other components, dosages, and preparation processes are exactly the same as in Example 1.
[0073] Comparative Example 6 The only difference between this comparative example and Example 1 is that in step S6, the programmed ripening is cancelled and replaced with continuous static ripening at 5°C for 13 hours. All other process parameters are exactly the same as in Example 1.
[0074] I. In vitro sustained-release performance test The dissolution test was conducted according to the third method of the dissolution test, General Chapter 0931, Part IV of the 2020 edition of the Chinese Pharmacopoeia. 5g of each of the ophthalmic sustained-release gel formulations of Examples 1-3 and Comparative Examples 1-6 were placed in dissolution cups. 500mL of simulated tear fluid containing 0.5% Tween 80 in pH 7.4 phosphate buffer was used as the release medium. The medium temperature was set at 34℃±0.5℃ to simulate the temperature of the eye, and the stirring speed was 50rpm. At sampling time points of 48h, 120h, 168h, 216h, 240h, 288h, 312h, and 336h, 10mL of release medium was aspirated using an automated sampler, and an equal volume of isothermal fresh simulated tears was added simultaneously. The aspirated samples were filtered through a 0.22μm filter membrane, and the concentrations of the active drugs latanoprost, tafluprost, or bimproporst in the filtrate were determined using high-performance liquid chromatography (HPLC). The cumulative release rate at each time point was calculated, and in vitro release curves were plotted. The sustained-release performance advantages of different formulations were evaluated by comparing the cumulative release rate, release half-life, and the stability of the release curves. The release half-life was calculated using a Weibull model, and release stability was expressed as the coefficient of variation of the cumulative release rate over 48h.
[0075] II. In vitro corneal permeability test The test was conducted according to the Franz diffusion cell method, Method 5, Drug Release Assay, Part IV, General Chapter 0931, Chinese Pharmacopoeia 2020 Edition. Healthy rabbits weighing 2.0-2.5 kg were selected. After euthanasia, the eyeballs were quickly removed, the cornea was dissected, and the connective tissue on the surface of the corneal epithelium was removed. The cornea was fixed between the supply chamber and the receiving chamber of the Franz diffusion cell, ensuring that the corneal epithelium faced the supply chamber. 30 mL of pH 7.4 phosphate buffer solution at 34℃±0.5℃ was added to the receiving chamber. Nitrogen gas was continuously purged to ensure sufficient dissolved oxygen. The stirring speed was 100 rpm. After equilibration for 30 min, 0.2 g of each of the ophthalmic sustained-release gel formulations from Examples 1-3 and Comparative Examples 1-6 were evenly applied to the surface of the corneal epithelium. At sampling time points of 1h, 2h, 4h, 6h, 8h, 12h, and 24h, 5mL of buffer solution was aspirated from the receiving chamber, and an equal volume of isothermal fresh buffer solution was added simultaneously. After filtration through a 0.22μm filter membrane, the drug concentration was determined by high-performance liquid chromatography (HPLC), and the cumulative permeation per unit area of the cornea was calculated. The corneal permeation coefficient Papp was calculated using Origin software to compare the corneal permeation efficiency of different formulations. The permeation coefficient was calculated using the formula Papp = (dQ / dt) / (C0 × A), where dQ / dt represents the steady-state permeation rate of the drug, C0 represents the initial drug concentration in the supply chamber, and A represents the effective permeation area of the cornea.
[0076] III. Mucosal Adhesion Test The tensile testing method was used to test the adhesion of medical materials using the tensile testing machine, in accordance with the industry standard YY / T1598-2018. Porcine gastric mucosa, similar in characteristics to ocular mucosa, was selected as a simulated mucosa. This mucosa was rinsed with physiological saline and cut into 2cm × 2cm pieces. The porcine gastric mucosa was fixed to the lower clamp of the tensile testing machine. 0.1g of each of the ophthalmic sustained-release gel formulations from Examples 1-3 and Comparative Examples 1-6 was evenly applied to the mucosa surface. The upper clamp of the tensile testing machine was quickly pressed onto the gel surface with a contact area of 1cm², and a pre-pressure of 0.5N was applied and held for 30s. The peeling rate of the tensile testing machine was set to 10mm / min, and the test temperature was 34℃ ± 0.5℃. The maximum and average peeling forces were recorded during the test. Each sample was tested in parallel five times, and the average value was used as the evaluation index of mucosal adhesion. The shape of the force-displacement curve during the peeling process was also recorded. The smoother the curve and the greater the maximum and average peel force, the better the mucosal adhesion performance. By comparing the adhesion force data of different formulations, we can reflect the influence of mucosal adhesion, penetration enhancers and formulation system on adhesion performance.
[0077] The results of the in vitro sustained-release performance test are shown in Table 1.
[0078] Table 1:
[0079] The results of the in vitro corneal permeability test are shown in Table 2.
[0080] Table 2:
[0081] The results of the mucosal adhesion test are shown in Table 3.
[0082] Table 3:
[0083] As can be seen from Examples 1-3 and Comparative Example 1, and Tables 1-3, there is a synergistic effect between the oleate compound and the structured phospholipid. Both participate in the co-assembly process of the dispersion, maintaining the integrity and stability of the dispersion structure. This synergistic effect not only affects the encapsulation state of the drug in the gel matrix but also indirectly affects the interaction between the gel and the corneal mucosa. Without the oleate compound, the dispersion cannot form a stable structure, leading to a decrease in the ability to regulate drug release, reduced carrier delivery efficiency during corneal penetration, and weakened binding ability between the gel system and the mucosal surface, thus affecting the core performance of the overall product.
[0084] As can be seen from Examples 1-3 and Comparative Example 2, and in conjunction with Tables 1-3, the structural characteristics of oleate compounds have a significant impact on formulation performance. Oleate esters with different structures exhibit differences in compatibility and interaction strength with structured phospholipids and block copolymers. The structure of p-hydroxyphenylethanol oleate is better suited to the assembly requirements of each component in the formulation system, enabling it to better participate in dispersion formation and synergistically interact with the gel matrix. In contrast, the replaced oleate esters, due to structural differences, cannot achieve the same level of inter-component synergistic effect, leading to corresponding changes in drug release stability, corneal penetration efficiency, and mucosal adhesion stability.
[0085] As can be seen from Examples 1-3 and Comparative Example 3, and in conjunction with Tables 1-3, structured phospholipids are key components in the dispersion formation process, and their co-assembly with oleate compounds is crucial for maintaining dispersion stability. Structured phospholipids can regulate the surface properties and particle size distribution of the dispersion through their structural characteristics, providing a stable encapsulation environment for the drug. Simultaneously, during corneal penetration, they facilitate the interaction between the carrier and the corneal epithelium, promoting drug delivery. Without structured phospholipids, not only is dispersion formation hindered, but the overall structural uniformity of the gel system is also affected, leading to uncontrolled drug release, decreased penetration efficiency, and weakened adhesion properties.
[0086] As can be seen from Examples 1-3 and Comparative Example 4, and in conjunction with Tables 1-3, the PEG-modified groups of structured phospholipids play a crucial role in the formulation system. They can enhance the stability of the dispersion through steric hindrance, reduce aggregation between components, and improve the compatibility of the gel system with biological mucosa. Ordinary soybean lecithin, lacking this modified structure, cannot provide the same level of steric stability, leading to easily disrupted dispersion structures during co-assembly. This results in ineffective regulation of drug release, insufficient carrier stability during corneal penetration, and compromised interaction strength between the gel and mucosal surface, ultimately manifesting as differences in various properties.
[0087] As can be seen from Examples 1-3 and Comparative Example 5, and in conjunction with Tables 1-3, the structural characteristics of the block copolymer directly determine the performance of the gel matrix. The polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, through the controlled ratio of hydrophobic to hydrophilic segments, can form a gel network with suitable swelling properties and stability, providing a foundation for sustained drug release. Different types of thermosensitive polymers differ in segmental interactions, network-forming capabilities, and compatibility with other components. Replaced polymers cannot form gel matrices with equivalent structures, resulting in poor drug encapsulation, unstable release, and significantly affected gel adhesion to the corneal mucosa and its role in promoting drug penetration.
[0088] As can be seen from Examples 1-3 and Comparative Example 6, and in conjunction with Tables 1-3, the programmed maturation process is a key step in optimizing the gel network structure. The combination of low-temperature static setting and programmed temperature rise promotes the uniform formation of the gel network, allowing the drug, dispersion, and gel matrix to fully integrate and reducing phase separation within the system. Simple low-temperature continuous maturation lacks the regulatory effect of a temperature gradient, failing to achieve refined gel network construction. This results in insufficient gel structure uniformity, uneven drug distribution within the system, and consequently affects the stability of drug release. It also weakens the binding stability between the gel and the mucosal surface, as well as the efficiency of drug penetration and delivery.
[0089] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An ophthalmic sustained release adhesive gel comprising a copolymer and an oleate, characterized in that: made from the following components by weight: block copolymer 32-40 parts, oleate compound 3.0-5.0 parts, active drug 0.1-0.2 parts, structured phospholipid 1.6-2.0 parts, mucous membrane adhesion and penetration enhancer 1.2-1.6 parts, antioxidant stabilizer 0.6-1.0 parts, osmotic pressure regulator 4.0-6.0 parts, pH regulator 1.3-1.5 parts, preservative 0.02-0.06 parts, water for injection 350-400 parts.
2. An ocular sustained release adhesive gel containing a copolymer with oleate according to claim 1, characterized by: made from the following components by weight: block copolymer 36 parts, oleate compound 4.0 parts, active drug 0.15 parts, structured phospholipid 1.8 parts, mucous membrane adhesion and penetration enhancer 1.4 parts, antioxidant stabilizer 0.8 parts, osmotic pressure regulator 5.0 parts, pH regulator 1.4 parts, preservative 0.04 parts, water for injection 375 parts.
3. An ocular sustained release adhesive gel containing a copolymer with oleate according to claim 1, characterized by: The block copolymer is polycaprolactone-polyethylene glycol-polycaprolactone triblock copolymer, wherein the mass ratio of polycaprolactone segment to polyethylene glycol segment is 1.8:1 to 2.5:1, and the number average molecular weight of the polyethylene glycol segment is 1500-2500; the oleate compound is p-hydroxyphenyl ethanol oleate; and the structured phospholipid is distearoyl phosphatidyl ethanolamine-polyethylene glycol 2000.
4. The ocular sustained release adhesive gel containing a copolymer and an oleate of claim 1, wherein: The active drug is at least one of latanoprost, tafluprost or bimatoprost; and the antioxidant stabilizer is at least one of DL-α-tocopherol polyethylene glycol succinate or sodium bisulfite.
5. The ocular sustained release adhesive gel containing copolymer with oleate of claim 1, wherein: The mucous membrane adhesion and penetration enhancer is a graft copolymer of sodium hyaluronate and chitosan hydrochloride connected by amide bond, with a number average molecular weight of 8000-20000, and the mass ratio of sodium hyaluronate to chitosan hydrochloride is 1:0.5 to 1:2; the osmotic pressure regulator is at least one of sodium chloride and mannitol; the pH regulator is at least one of sodium phosphate dibasic-sodium phosphate monobasic buffer pair and triethanolamine, for adjusting and maintaining the pH value of the preparation at 6.8-7.2; and the preservative is at least one of benzalkonium chloride, potassium sorbate or phenoxyethanol.
6. A process for the preparation of an ophthalmic sustained release adhesive gel containing a copolymer and an oleate, characterized in that, An eye sustained-release adhesive gel containing copolymer and oleate for use in any one of claims 1-5, comprising the following steps: S1, preparation of co-assembled dispersion: dissolving the oleate compound and the structured phospholipid in anhydrous ethanol together, injecting the solution into preheated water for injection under nitrogen protection, and then performing high-pressure microfluidization homogenization to obtain a dispersion; S2, treatment of active drug: dissolving the active drug in ethanol, adding the solution dropwise into part of the water for injection under ice bath and ultrasonic assistance, and then performing high-pressure homogenization to obtain a drug suspension; S3, swelling and formation of gel matrix: dispersing the block copolymer in the remaining water for injection, swelling at low temperature, and then stirring to form a uniform transparent gel matrix solution under warming conditions; S4, stepwise mixing: first mixing and stirring the dispersion and the gel matrix solution, then slowly adding the drug suspension into the mixed system, and then homogenizing after cooling and stirring. S5, function of auxiliary materials integration and ultrasonic treatment: adding the formula amount of mucosal adhesion and penetration enhancer, antioxidant stabilizer, osmotic pressure regulator and preservative to the mixed system in turn, stirring each auxiliary material to dissolve or disperse, then carrying out intermittent ultrasonic treatment on the whole system in ice water bath; S6, pH adjustment and programmed maturation: adding pH regulator to adjust the pH value of the system to the eye applicable range, then standing at low temperature for maturation, and then programmed warming to near body temperature for maturation; S7, terminal sterilization and packaging: the matured gel is filtered through two-stage microporous filter membrane for sterilization, and then filled and sealed under sterile environment.
7. A process for the preparation of an ocular sustained release adhesive gel containing copolymer and oleate according to claim 6, characterized by: In step S1, the preheated injection water has a temperature of 50-60℃, and its amount accounts for 25-35% of the total weight of injection water; the high-pressure microfluidization homogenization treatment has a pressure of 80-120MPa and a cycle number of 3-4 times; the volume of anhydrous ethanol accounts for 4-6 times of the total mass of oleate compound and structured phospholipid; in step S2, the volume of ethanol used for dissolving active drugs is 8-12 times of the weight of active drugs; the partial injection water accounts for 10-15% of the total weight of injection water; the high-pressure homogenization treatment has a pressure of 60-100MPa and a treatment number of 2-4 times.
8. A process for the preparation of an ocular sustained release adhesive gel containing copolymer and oleate as claimed in claim 6, wherein: In step S3, the low temperature is 4-8℃, and the swelling time is 3-5 hours; the warming condition is 35-40℃, and the stirring speed is 300-400rpm; in step S4, the mixing temperature of the dispersion and the gel matrix solution is 35-40℃, and the stirring time is 1-2 hours; after dropping, the temperature is lowered to 20-25℃, the stirring speed is 500-600rpm, and the homogenization time is 1-1.5 hours.
9. A process for the preparation of an ocular sustained release adhesive gel containing copolymer and oleate as claimed in claim 6, wherein: In step S5, the stirring speed is 200-300rpm, and the time is 15-25 minutes; the intermittent ultrasonic treatment has a power of 150-250W and a frequency of 25-35kHz, adopts a mode of working for 2-3 seconds and intermittently for 3-4 seconds, and the total treatment time is 8-15 minutes.
10. A process for the preparation of an ocular sustained release adhesive gel containing copolymer and oleate as claimed in claim 6, wherein: In step S6, the eye applicable pH range is 6.9-7.1; the low-temperature standing maturation is standing at 4-6℃ for 8-12 hours; the programmed warming rate is 0.2-0.5℃ / min, the near body temperature is 25-30℃, and the continuous maturation time is 2-4 hours; in step S7, the two-stage microporous filter membrane is a polyether sulfone filter membrane with a pore size of 0.45μm and 0.22μm; the container is replaced with nitrogen for three times before filling, and each replacement lasts for 10-15 seconds.
Citation Information
Patent Citations
Ophthalmic temperature-sensitive in-situ gel preparation containing Remdesivir as well as preparation method and application of ophthalmic temperature-sensitive in-situ gel preparation
CN113559056A